Transportation and adhesion of asphaltenes in a heat exchanger tube through CFD simulations - Emani, S. (American Institute of Physics Inc., 2017)
Asphaltenes are identified as the main cause of crude oil fouling in preheat trains. The understanding of individual trajectory of asphaltenes particles, transportation behavior of the fouling precursors in the domain and the effect of various attractive and/or repulsive forces acting on the asphaltenes particles, which lead to an increase/decrease in the deposition, have been impeded by a shortage of information. In the present work, an attempt has been made to understand the transportation and adhesion behavior of asphaltenes in a heat exchanger tube through Computational Fluid Dynamics approach. A Lagrangian based discrete-phase model has been implemented to understand the hydrodynamics of asphaltenes particles and the effect of various forces on the asphaltenes particles deposition on the heat transfer surfaces. The effect of wall shear stress, surface roughness, and temperature difference on asphaltenes deposition is also reported. From the CFD analysis, the net mass deposition of the asphaltenes particles is minimized with an increase in wall shear stress and surface roughness. The asphaltenes particles in the region where the temperature difference between the bulk and wall is lower at a constant wall temperature are carried forward with the flow and particles with higher temperature difference between the bulk and wall at constant wall temperature are attracted towards the heat transfer surface and deposited on the wall of the heat exchanger tube. © 2017 Author(s).